PENGGUNAAN METODE PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETRAMPILAN PENGISIAN PARTOGRAF PADA MAHASISWA SEMESTER III DI PRODI KEBIDANAN (D III) UNIVERSITAS KADIRI TAHUN 2016 - Dessy Lutfiasari; Dhita Kris Prasetyanti (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Based on interview result that on;y 4 (40%) knows and can fill the partograph correctly. This fact knows that there are lack of knowing to fill partograph correctly. The aim of this research is to know the influence of problem based learning method through partograph filling skill on the 3rd semester of midwifery student of kadiri University 2016. Research design use quasy experiment with Pretest Posttest two Group Design. Responden of this research are 32 student of midwifery student. The result of this research are mean of partograph filling skill on intervention group is 72,631 beside on control group is 57,731. Mann whitney statistic show that ρ value = 0,002 which p < α = 0,05 its mean that there are influences of problem based learning method through partograph filling skill on the 3rd semester of midwifery student of kadiri University 2016.